Molecular testing for the clinical diagnosis of fibrolamellar carcinoma - Graham, Rondell P.; Rössler, Stephanie; Schirmacher, Peter (Modern pathology, 2018)
Fibrolamellar carcinoma has a distinctive morphology and immunophenotype, including cytokeratin 7 and CD68 co-expression. Despite the distinct findings, accurate diagnosis of fibrolamellar carcinoma continues to be a challenge. Recently, fibrolamellar carcinomas were found to harbor a characteristic somatic gene fusion, DNAJB1-PRKACA. A break-apart fluorescence in situ hybridization (FISH) assay was designed to detect this fusion event and to examine its diagnostic performance in a large, multicenter, multinational study. Cases initially classified as fibrolamellar carcinoma based on histological features were reviewed from 124 patients. Upon central review, 104 of the 124 cases were classified histologically as typical of fibrolamellar carcinoma, 12 cases as ‘possible fibrolamellar carcinoma’ and 8 cases as ‘unlikely to be fibrolamellar carcinoma’. PRKACA FISH was positive for rearrangement in 102 of 103 (99%) typical fibrolamellar carcinomas, 9 of 12 ‘possible fibrolamellar carcinomas’ and 0 of 8 cases ‘unlikely to be fibrolamellar carcinomas’. Within the morphologically typical group of fibrolamellar carcinomas, two tumors with unusual FISH patterns were also identified. Both cases had the fusion gene DNAJB1-PRKACA, but one also had amplification of the fusion gene and one had heterozygous deletion of the normal PRKACA locus. In addition, 88 conventional hepatocellular carcinomas were evaluated with PRKACA FISH and all were negative. These findings demonstrate that FISH for the PRKACA rearrangement is a clinically useful tool to confirm the diagnosis of fibrolamellar carcinoma, with high sensitivity and specificity. A diagnosis of fibrolamellar carcinoma is more accurate when based on morphology plus confirmatory testing than when based on morphology alone.